Raman Open Database: first interconnected Raman–X‐ray diffraction open‐access resource for material identification. Issue 3 (28th May 2019) - El Mendili, Yassine; Vaitkus, Antanas; Merkys, Andrius; Gražulis, Saulius; Chateigner, Daniel; Mathevet, Fabrice; Gascoin, Stéphanie; Petit, Sebastien; Bardeau, Jean-François; Zanatta, Marco; Secchi, Maria; Mariotto, Gino; et al.
Abstract : The fully open character of the Raman Open Database makes this novel database freely and completely usable by anybody worldwide: academics, those working in industry and the general public. Abstract : Detailed crystallographic information provided by X‐ray diffraction (XRD) is complementary to molecular information provided by Raman spectroscopy. Accordingly, the combined use of these techniques allows the identification of an unknown compound without ambiguity. However, a full combination of Raman and XRD results requires an appropriate and reliable reference database with complete information. This is already available for XRD. The main objective of this paper is to introduce and describe the recently developed Raman Open Database (ROD, http://solsa.crystallography.net/rod ). It comprises a collection of high‐quality uncorrected Raman spectra. The novelty of this database is its interconnectedness with other open databases like the Crystallography Open Database (http://www.crystallography.net/cod and Theoretical Crystallography Open Database (http://www.crystallography.net/tcod/ ). The syntax adopted to format entries in the ROD is based on the worldwide recognized and used CIF format, which offers a simple way for data exchange, writing and description. ROD also uses JCAMP‐DX files as an alternative format for submitted spectra. JCAMP‐DX files are compatible to varying degrees with most commercial Raman software and can be read and edited using standard text editors.